1999
DOI: 10.1128/jb.181.17.5140-5148.1999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acyl Coenzyme A Oxidase (Aox) Isozyme Function in the n -Alkane-Assimilating Yeast Yarrowia lipolytica

Abstract: We have identified five acyl coenzyme A (CoA) oxidase isozymes (Aox1 through Aox5) in the n-alkane-assimilating yeastYarrowia lipolytica, encoded by the POX1through POX5 genes. The physiological function of these oxidases has been investigated by gene disruption. Single, double, triple, and quadruple disruptants were constructed. Global Aox activity was determined as a function of time after induction and of substrate chain length. Single null mutations did not affect growth but affected the chain length prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(59 citation statements)
references
References 41 publications
(42 reference statements)
3
55
0
1
Order By: Relevance
“…POX1 does not contribute to Aox activity, POX2 and POX3 code for the long-and short-chain specific Aox, respectively, and account for 80% of total Aox activity, POX4 codes for the minor Aox and POX5 codes for a nonspecific chain length Aox that is responsible for the remaining Aox activity. Only the Dpox2, 3, 4, 5 quadruple null mutant has the complete growth defect in oleic acid medium (Wang et al, 1999). No one Aox isoform contains a conserved variant of a C-terminal peroxisomal targeting signal 1 (PTS1) or an N-terminal PTS2, though all five Aox isoforms are peroxisomal in Y. lipolytica.…”
Section: Introductionmentioning
confidence: 99%
“…POX1 does not contribute to Aox activity, POX2 and POX3 code for the long-and short-chain specific Aox, respectively, and account for 80% of total Aox activity, POX4 codes for the minor Aox and POX5 codes for a nonspecific chain length Aox that is responsible for the remaining Aox activity. Only the Dpox2, 3, 4, 5 quadruple null mutant has the complete growth defect in oleic acid medium (Wang et al, 1999). No one Aox isoform contains a conserved variant of a C-terminal peroxisomal targeting signal 1 (PTS1) or an N-terminal PTS2, though all five Aox isoforms are peroxisomal in Y. lipolytica.…”
Section: Introductionmentioning
confidence: 99%
“…During the -oxidation process, six peroxisomal acyl-CoA oxidases (AOX1-6) encoded by Pox1-6 genes are identified as chainlength-specific for fatty acid degradation [106][107][108][109]. Previous studies demonstrated that the Y. lipolytica strains with Pox1-6 gene mutations impaired fatty acid degrading ability resulting in the increase of high-lipid content in biomass [86,[110][111][112][113]. The next two steps of the -oxidation are catalyzed by the multifunctional enzyme (MFE) [218,219].…”
Section: Hydrophobic Substratesmentioning
confidence: 99%
“…Because of the large number of genetic markers and molecular tools available, this yeast is considered an efficient heterologous protein production system (Muller et al, 1998;Gasmi et al, 2011;Rao et al, 2011). Several Y. lipolytica promoters have been used for recombinant protein expression (Domínguez et al, 1998;Muller et al, 1998;Wang et al, 1999;Pignède et al, 2000). The copper-inducible bi-directional promoter of YlMTPI and YlMTPII genes has been characterized previously (García, 1993;Domínguez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%